PENETAPAN KELAS KEMAMPUAN LAHAN DAS WAE BATU MERAH KOTA AMBON PROVINSI MALUKU - Dhanang Supriadi; Rafael M Osok; Silwanus M Talakua (JURNAL BUDIDAYA PERTANIAN, 2017)
A research had been held from July till October 2016 in Wae Batu Merah Watershed, at Ambon City Maluku, Maluku Province with area covered 685,14 ha including in the area of Batu Merah Village and a part of Soya Village. The aim of the research were to: 1) determine land capability class; 2) determine land capability class with different topographyc classes, soil types and land use types; and 3) determine land use direction corresponding to each land capability class. The research method was a survey method with a pattern of synthetic and analytical approach using a flexible range of observation following the change in shape of physiography and land use. The results showed that: 1) The Wae Batu Merah Watershed has 6 land capability classes, i.e class II, III, IV, VI, VII, VIII, 2) Based on the different topography classses, soil types, and land use types it was found that land capability class with limiting factors were influenced of the three, 3) The direction of land use in the Wae Batu Merah Watershed were: intensive, middle and limited agricultural with agroforestry system, middle and limited pastural with agroforestry system, protected forest area, forest, resettlement cropping, biopore, and organic matter.